Challenging normativity: experiences in queerifying the classroom - Requena-Pelegrí, Teresa; López-Sánchez, Gemma; Aaouinti-Haris, Asmaa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
As English Studies researchers and teachers, our experience has shown that there continues to exist an urgent need to incorporate gender as a reading tool of literary texts to foster a non-discriminatory and equality perspective. Given the many advances in gender equality that have been achieved as well as the rising backlash against such progressive moves that spread through Europe, our proposal is based on the “queerification of the classroom”, a notion defined as a transgressive initiative that effectively and systematically incorporates the deconstruction of normativity and fosters resistance to socially constructed assumptions about normativity and deviance.